A silicon Hall sensor SoC for current sensors. (August 2019) - Girgin, Alper; Bilmez, Melih; Amin, Hamid Yadegar; Karalar, Tufan Coşkun
Abstract: In this paper we present a System on Chip (SoC) that implements a Hall Effect Sensor along with its readout circuits and calibration support. The sensor is designed for use in Hall effect based current sensors. The SoC was implemented in 0.18u CMOS technology and integrates Hall sense elements, preamplifiers as well as a delta sigma ADC, a DAC and a digital calibration. The SoC achieves 11 V/T gain and 0.76% RMS accuracy over a range of ±300 mT and 30 kHz signal bandwidth. The SoC integrates a digital correction unit that implements a polynomial computation algorithm for calibrating out the current sensor's magnetic core induced nonlinearities. Offset temperature drift of the sensor is 6.81μT per degrees over −40 °C to 85 °C range. A current sensor is built using the SoC. It can measure currents from −10 A to 10 A and achieve 1.67% RMS measurement accuracy.